Diffusion Length Measurements of Microcrystalline Silicon Thin Films Prepared by Hot-wire/Catalytic Chemical Vapor Deposition (hwcvd) - Okur, Salih; Güneş, Mehmet; Güneş, Mehmet; Finger, Friedhelm; Okur, Salih; Carius, Reinhard (Elsevier Ltd., 2006)
Hydrogenated microcrystalline silicon (μc-Si:H) films prepared by using the hot-wire/catalytic chemical vapor deposition (HWCVD) technique at low substrate temperatures between 185 °C and 220 °C with different silane concentrations (SC) were investigated using steady-state photocarrier grating (SSPG) and the steady-state photoconductivity methods (SSPC). Crystalline volume fractions (IC RS) obtained from Raman spectroscopy change from 0.22 to 0.77. The diffusion length (LD) is measured at generation rates between G = 1019 and 1021 cm- 3 s- 1. LD changes from 27 nm to 270 nm, with maximum values around SC = 5%. The dependence of LD on SC is similar to that observed for similar quality microcrystalline silicon films prepared using the VHF-PECVD technique. The grating quality factor, γ0, drops from about 0.9 to 0.5 after transition to the microcrystalline regime as indication of scattering from surface patterns.
Proceedings of the Third International Conference on Hot-Wire; 23 August 2004 through 27 August 2004
Keywords: Thin films; Diffusion length; Hot-wire/catalytic chemical vapor deposition; Raman spectroscopy